Freedom Of Determination Of Maximum Criminal Prosecution Plan By The Public Prosecutor - Taufik eka purwanto, S.H; prof. Dr. I Nyoman Nurjaya, S.H., M.H; Dr. Iwan Permadi, SH.,MH (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The Public Prosecutor has the authority and responsibility to prosecute the case and prove what is alleged before the trial. Before determining criminal charges, there is a mechanism for submitting a proposed prosecution plan by the Public Prosecutor with the issuance of a prosecution plan (P-41), which contains a proposal from the Public Prosecutor who hears the case, then given advice by the Head of the Public Criminal Section and given the Opinion of the Chief Prosecutor of his work unit. On the opinion of the Chief Prosecutor of the work unit that must be read by the Public Prosecutor in front of the trial. The claim can certainly be contrary to the conscience of the Public Prosecutor who conducts evidence in the trial, either from the length of the criminal or the article that must be proven. In this title, the author will analyze the application of equity or equality of the prosecutor's position in the preparation of the prosecution plan if applied in the Indonesian criminal justice system. The research method used by the author is normative research from literature studies and materials obtained systematically compiled which is preceded by preliminary analysis continued with data analysis and discussion results and ends with conclusions. This paper aims to describe the circumstances or symptoms of an object that is thoroughly and systematically examined. In addition, to be a new reference to the freedom of prosecution of the prosecution plan because throughout the search is still very lacking references related to the application of equality or some kind of dissenting opinion from the Prosecutor in the preparation of the prosecution plan against criminal cases.